Kültür Endüstrisi Kavramı Çerçevesinde Medya Ürünleri: Eleştirel Yaklaşım - Kara, Tolga (The Turkish Online Journal of Design Art and Communication, 2014)
Considerations of media products sometimes assume that media share similar economic and business characteristics and that media are no different from other products and services. They express the view that no more differences need to be recognized for media then the kinds of differences observed between manufacturing automobiles and forniture products. This view is problematic, however, because media products differ significantly among themselves and because they operate in economic environments with business dynamics that most other products and services do not encounter. This article aims to discussion how media products differ among themselves and how those differences affect the economic forces they encounter and business dynamics of their industries in the context of Adorna and Horkheimer’s “Culture Industry”concept. It also examined supply side and demand side differences between media and other products and how these affect media industry business dynamics.
Keywords: Medyada Ürün Yönetimi; Medya Ekonomisi; Medya Endüstrisi ve Ürünleri; Product Management in Media; Media Economics; Media Industry and Product